Rancang Bangun Pembangkit Listrik Alternatif dengan Bantuan Pully dan Belt Motor DC sebagai Penggerak Alternator - Sofiah, Sofiah; Hurairah, Muhammad (UNIVERSITAS MUHAMMADIYAH PALEMBANG, 2020)
ABSTRAC Electricity is a source of energy that is widely used for the needs of household electrical appliances that are needed within 24 hours of continuously supplying electricity. Most of the mains voltage is supplied from the state 220 volt. When the electricity goes out, the electrical equipment cannot function properly, therefore there must be an alternative source of electricity to replace it. The purpose of this research is to design an alternative power plant from the initial drive system of a dc motor with mechanical motion transfer using pully and van belt as the drive for the dc alternator. The research method used in this research has the following stages: 1). Designing a dc motor and a dc alternator as a producer of electrical energy, 2). Installing AS bearings, vanbelt and pully, 3). testing and measuring dc motors and dc alternators, 4). Calculate and analyze the design results. From this research, the direct current generated by the accumulator with a voltage of 12 Vdc with a current charge of 10 AH, so that it can be used to turn on the inverter as a means of converting the voltage of a direct power source into an alternating current with a voltage of 220 V to turn on household electrical appliances when supplied. from PLN experiencing a blackout. So that our daily work can run smoothly without any constraints on the flow of electricity.Keywords: MotorDC, PullyVanBelt, Alternator